Improving the Quality of Human Resources in Indigenous Village Institutions Through Work Culture Based on "Catur Marga" in Bali Aga Village, Buleleng Regency - Luh Kartika Ningsih; Ni Luh Putu Eka Yudi Prastiwi (International Journal of Social Science and Business, 2019)
This study aims to determine the improvement of human resources quality of the Village Institution through Catur Marga-based Work Culture in Bali Aga Village, Buleleng Regency. A quantitative approach will be used in this study. The data analysis technique used in this study was SEM PLS Version 3.0. The sample is 135 people with t-table values for the significance level α = 0.05 of 1.960. The results showed that there was a positive and significant result in all relationships where the Effect of Catur Marga-based Work Culture on HRM was 4.477. Likewise, the Effect of Catur Marga-based Work Culture on Work Productivity was 31.010, and the relationship of Human Resource Management to Work Productivity was 7.338. From the results, it can be concluded that Catur Marga- based culture work has a positive role because it can provide good results for improving the Quality of Human Resource Management and Work Productivity.